Literasi Keuangan dan Self-Efficacy sebagai Penggerak Kinerja UMKM Tenun Ikat Sumba - Bulu, Anastasia Natalia Yesi Ngongo (Magister Manajemen Universitas Wisnuwardhana, 2025)
This study aims to analyze the effect of financial literacy on the performance of tenun ikat artisans in Southwest Sumba Regency, East Nusa Tenggara, with financial self-efficacy as a mediating variable. Data were collected from 47 respondents through questionnaires and analyzed using Partial Least Squares (PLS). The results show that financial literacy does not have a significant direct effect on MSME performance but significantly improves financial self-efficacy. Financial self-efficacy has a significant positive effect on MSME performance and fully mediates the relationship between financial literacy and MSME performance. These findings suggest that improving financial literacy must be accompanied by enhancing financial self-efficacy to improve MSME performance. Local governments are recommended to provide contextual financial literacy training and empowerment programs based on self-efficacy development.